The impact of air pollution on petcare utilization - Stephen Jarvis; Olivier Deschenes; Akshaya Jha; Alan D. Radford (Proceedings of the National Academy of Sciences, 2025)
Air pollution is one of the leading causes of morbidity and premature mortality globally. A large literature documents the adverse impacts of ambient air pollution on human health. In contrast, there is a lack of comparable research studying the effects of air pollution on animal health. We fill this gap, utilizing 5 y of data on over seven million visits to veterinary practices across the United Kingdom. Leveraging within-city variation in daily monitor-measured air pollution levels, we find that increases in fine particulate matter (i.e., PM 2.5 ) are associated with significant increases in the number of vet visits for both cats and dogs. In aggregate, these estimates suggest that reducing ambient PM 2.5 levels to a maximum of 5 μg per cubic meter as recommended by the World Health Organization would result in a 0.7 to 2.5% reduction in vet visits.